2009
DOI: 10.1590/s0100-736x2009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos morfológicos da ultra-sonografia hepática de ovinos

Abstract: RESUMO.-A ultra-sonografia (US) é uma das técnicas de exame complementar eletivas para o diagnóstico de enfermidades hepáticas de diversas espécies domésti-cas. Em ovinos, no entanto, existem poucos relatos sobre o aspecto ultra-sonográfico de enfermidades hepáti-cas e não há definição precisa dos padrões anatômicos da US normal do fígado. Neste estudo foram utilizados 58 ovinos da raça Santa Inês: n1=8 machos, n2=10 fêmeas não gestantes e n3=40 fêmeas gestantes. Os animais foram escaneados do 12º ao 8º espaço… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
0
0
2
Order By: Relevance
“…However, in the present study, hyperechogenicity was considered to be an alteration, because the animals were not subjected to anesthesia during the exam. The gallbladder showed features similar to those described in capuchin monkeys [1], rhesus monkeys [28], and other species, such as dogs, cats [20], and sheep [19]. Hepatic veins are associated with the inferior vena cava and appear sonographically as 'slits' in the hepatic parenchyma.…”
Section: Discussionsupporting
confidence: 59%
“…However, in the present study, hyperechogenicity was considered to be an alteration, because the animals were not subjected to anesthesia during the exam. The gallbladder showed features similar to those described in capuchin monkeys [1], rhesus monkeys [28], and other species, such as dogs, cats [20], and sheep [19]. Hepatic veins are associated with the inferior vena cava and appear sonographically as 'slits' in the hepatic parenchyma.…”
Section: Discussionsupporting
confidence: 59%
“…The ultrasonographic evaluations were performed as per Néspoli et al (2009) in the right antimere of the rib cage between the 8 th and 11 th intercostal spaces, demonstrating that, in sheep, the liver can be scanned from the 8 th to the 12 th intercostal space. This evaluation revealed that the liver increased in size in all the animals over time, and the points used for the liver biopsies became increasingly caudal.…”
Section: Resultsmentioning
confidence: 99%
“…Os ovinos afetados apresentavam um quadro típico de ascite devido a fibrose hepática difusa. O exame ultrassonográfico hepático em ovinos proporciona avaliação mais detalhada da arquitetura interna hepática, incluindo a vascularização e o sistema biliar [9]. Os principais achados ultrassonográficos consistiram de paredes dos vasos hepáticos pouco distintas (supressão das margens), veia cava caudal com diâmetro aumentado, parênquima levemente heterogêneo e com ecogenicidade maior que a cortical renal direita.…”
Section: Discussionunclassified
“…Foram coletadas amostras sanguíneas de dois ovinos do Surto 1 (Ovinos 1 e 2) e um ovino do Surto Em um dos ovinos (Ovino 1), realizou-se ultrassonografia abdominal com aparelho de ultrassonografia Logiq 100 Pro 1 equipado com transdutor linear de 5 MHz [9]. Após isso, o animal foi submetido a colocação de sonda de Foley (duas vias, n o 18) no abdômen ventro-lateral direito para drenagem de líquido ascítico (aproximadamente 13,5 litros); e, novamente submetido ao exame ultrassonográfico.…”
Section: Casosunclassified